Effects of cassava brown streak disease and harvest time on two cassava mosaic disease-resistant varieties in Eastern Democratic Republic of the Congo - Casinga, C.M.; Shirima, R.R.; Kangela, A.; Wosula, E.N.; Bashizi, B.; Ugentho, H.U.; Nabahungu, L.N.; Monde, G.; Bamba, Z.; Kumar, L.; Legg, J.P. (2025)
Cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) are the two main viral diseases threatening cassava production in the Democratic Republic of the Congo (DRC). CMD can be effectively controlled using resistant varieties; however, currently, there are no cassava varieties that exhibit durable resistance to CBSD. As the deleterious effects of CBSD become more pronounced with the maturity of the cassava, we assessed the potential benefits of early harvesting on mitigating the impact of CBSD on the performance of two improved CMD-resistant cassava varieties, Nabana (MM 96/4653) and Sawasawa (MM 96/3920). The percentage yield reduction was calculated by comparing the yield of infected treatments to that of uninfected treatments. At 9 months after planting (MAP) and 12 MAP, overall fresh root yield from farmer-selected healthy planting material of varieties Nabana and Sawasawa was significantly higher than the yield of crops established using CBSD-infected cuttings of the same varieties. Fresh root yield losses due to CBSD for Nabana were 44% at 9 MAP and 86% at 12 MAP, while for Sawasawa, they were 40% at 9 MAP and 72% at 12 MAP. Healthy planting material of the two varieties yielded 5% more at 12 MAP than at 9 MAP, while infected planting material yielded 52.5% less at 12 MAP than at 9 MAP. These results highlight the benefits of using healthy planting material in conjunction with early harvesting to minimize losses among CBSD-susceptible cassava varieties. These results suggest the need for a robust seed system that can deliver disease-free planting material of market-preferred varieties to farmers, thereby promoting food security.